PENGARUH PEMBERIAN BEBERAPA SUMBER UNSUR HARA N TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA - Megawati Siahaan; Arief Setiawan Sutanto; Sion Calvin Simanjuntak (Jurnal Agro Estate, 2021)
The establishment of oil palm plantations is starting from nursery which criteria has been standardized by the seeds produced. Nitrogen is one of the essential nutrients which determine the growth of oil palm (Elaeis guinensis Jacq) at the main nursery. Nitrogen has many sources which are produced from synthetics or natural sources, but on the other side, the pricing of fertilizers was increased any time and then must find an alternative which one is more effective and efficient. The effects of few nitrogen sources to the growth of oil palm in the main nursery is the objective of this research. The experiment was non factorial in a randomized complete block design comparing between N1 (urea Fertilizer), N2 (ZA Fertilizer), N3 (liquid organic fertilizer 60 ml/liter H2O had been extracted from Azolla microphylla), N4 (Azolla microphylla green manure 50 g/polybag) and N5 (Azolla microphylla composted 50 g/polybag) with five replications. The research showed that the height of oil palm in the nursery was not significantly affected by five nitrogen sources 2 and 4 weeks after treatment but significantly on 6, 8, 10 and 12 weeks, the higher plant found at N4 on12 weeks after treatment. Five Nitrogen sources were used not significantly affected amounts of leaves on 2 and 4 weeks but significantly affected on 6, 8, 10 and 12 weeks after applications. In the 12th week applications showed the most leaves on N3 but not significantly different from N4. Circumference of the stem after 2, 4, 6, 8 and 12 weeks after applications were not affected by five nitrogen sources but weight of the roots on fresh and dry conditions were affected by the treatment on 12th weeks which was N5 showed the highest but not different with N3 and N4; longs of the roots was not affected by the treatment. Composted, green manure as good as liquid organic fertilizer from Azolla microphylla had effects on amounts of leaves, height of plant, fresh and dry root weight. Azolla microphylla has the potential to be used as a source of nitrogen fertilizer on fertilizing oil palm at the main nursery.